1990
DOI: 10.1038/eye.1990.109
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between conjunctival provocation test (CPT) and systemic allergometric tests in allergic conjunctivitis

Abstract: In order to assess the potential usefulness of CPT as a diagnostic tool for ocular allergy, the correlation between skin/RAST tests and CPT was determined in 144 patients affected by allergic 'hay fever' type conjunctivitis. The results showed that an agreement between skin/RAST tests and CPT occurred in 71% of the cases (130/183). Of the 29% uncorrelated cases, 23% (43/183) were positive for at least one specific antigen by skin/RAST tests but not by CPT, while 6% (10/183) were positive for at least one speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…However, in our experience, we have found an approximately 60% to 70% correlation between positive skin tests and positive reaction to allergen instilled in the eye; therefore, if skin testing is solely relied on, some patients will be enrolled who might not have allergy to the pollen in season. Others have also seen a similar correlation [21]. Often, entry criteria require a patient to present in the office with a positive skin test and positive clinical signs and symptoms of ocular allergy.…”
Section: Factors Affecting Data In the Environmental Modelmentioning
confidence: 92%
“…However, in our experience, we have found an approximately 60% to 70% correlation between positive skin tests and positive reaction to allergen instilled in the eye; therefore, if skin testing is solely relied on, some patients will be enrolled who might not have allergy to the pollen in season. Others have also seen a similar correlation [21]. Often, entry criteria require a patient to present in the office with a positive skin test and positive clinical signs and symptoms of ocular allergy.…”
Section: Factors Affecting Data In the Environmental Modelmentioning
confidence: 92%
“…These studies suggested that CAC was helpful both in determining the etiology and diagnosis and therapy monitoring [29]. Some reports have also shown that patients allergic to common aeroallergens with negative SPT and suspected ocular allergic symptoms had a positive reaction to specific eye challenge [33,34,35]. CAC with latex was first described by Kurtz et al [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, direct mucosal allergen challenges, such as the conjunctival or nasal provocation test, are used as secondary diagnostic tools for a variety of purposes, for example: to confirm the diagnosis of occupational allergy; to confirm the diagnosis of seasonal allergic rhinitis and to exclude a clinical silent sensitization, if the result of a skin prick test or specific IgE measurement is contrary to the patient's clinical symptoms; assessing the symptoms directly at the organ level to evaluate the indication or efficacy of any antiallergic treatment, and to research the immunopathologic mechanisms in the target organs [7,10,11]. Nevertheless, different opinions exist in the literature as to whether the conjunctival provocation test (CPT) serves generally as a model of allergic rhinoconjunctivitis [7,12,13,14] or not [14,15]. The CPT has not yet been consistently defined by any international guidelines and is mentioned less often in the current literature [6,10].…”
Section: Introductionmentioning
confidence: 99%